Relationship between social media engagement and body shaming among Malaysian young adults - Wong, Jasmine Xin Lin; Labent, Shirly; Kong, Lek Chin; Siaw, Leng Chan (Human Resources Management Academic Research Society (HRMARS), 2024)
Body shaming is an unrepeated action in which a person expresses unsolicited, mostly negative opinions or comments about the target’s body, which can occur in social media and the real world. The primary purpose of this study was to determine the relationship between social media engagement and body shaming among Malaysian young adults. This study utilized a cross-sectional survey method. 193 respondents participated in this study and were selected through inclusion and exclusion criteria by purposive sampling. The data were collected through two questionnaires: the Social Media Engagement Questionnaire (SMEQ) to operationalize social media engagement and two subscales of the Objectified Body Consciousness Scale (OCBS), which is the Body Surveillance and Body Shame scale to measure the frequencies of respondents by monitoring their physical appearance. The finding demonstrated that the relationship between social media engagement and body surveillance showed a negative correlation relationship. The relationship between social media engagement and body shame obtained a positive correlation. Moreover, the relationship between body surveillance and body shame showed a positive relationship, and a significant gender difference was found in body shame. This study concluded that there is a relationship between social media engagement and body shaming among Malaysian young adults. The implications and future recommendations are discussed.